Effect of clinical doses of buserelin on in vivo bovine uterine activity at estrus - Dogan, Halef; Aydin, Muhterem (Tubitak Scientific & Technological Research Council Turkey, 2021)
For successful fertilization, a transfer system named rapid sperm transport generated by uterine contractions plays a crucial role. The purpose of this in vivo study was to investigate the effect of buserelin, a GnRH agonist widely used for ovulation induction after mating or artificial insemination, on bovine uterine contractility which supports rapid sperm transport at estrus. In vivo uterine contractile activity was measured by intrauterine pressure recording technique. In the study, the spontaneous uterine contractile activities of 28 cows at estrus were observed for 30 min. The cows were randomly divided into 4 treatment groups which have 7 cows each of and were injected appropriate agents as follows; two different clinical doses of buserelin (10.5 mu g, 21 mu g), oxytocin (50 IU) and control (placebo). Following treatment, drug-induced uterine activity was measured for 60 min. There were no differences in terms of frequency in all groups observed. Oxytocin which is known as an effective uterotonic increased the amplitude and area under curve of contraction at estrus. Two different doses of buserelin were observed to have no effect on uterine contractile activity in cows throughout 60 min. It was concluded that GnRH has no function on bovine uterine contractility which plays a role in sperm transportation at estrus.
Keywords: Buserelin; GnRH; uterine contractility; estrus; cow